Interpersonal Communication on the Performance of the Public Relations and Protocol Bureau of the Regional Secretariat of the Maluku Province - Jimmy Purwata Mangasi Sirait; Yuliana Lewanhila (Fakultas Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to analyze the effect of interpersonal communication on employee performance. The population used in this study were all 56 employees of the Public Relations and Protocol Bureau of the Maluku Province Regional Secretariat. The method of determining the sample is full sampling. Data were analyzed by multiple linear regression. The results of the study concluded that interpersonal communication in the dimensions of openness, empathy, support, positive feeling and equality had a positive and significant effect on performance, either partially or simultaneously.Â